(untitled) (International Journal of Engineering and Computer Science, 2015)
Random Early Detection [RED] algorithm achieves high throughput, packet delivery and low average end to end delay by stabilizing the average queue size through mapping the congestion into packet drop probability and detection and avoidance of incipient congestion. This paper includes the research work done in recent and modified mechanism to control the network congestion by maintaining the average queue length in acceptable range. This mechanism will avoid congestion, so that overall network performance will improve. Goal of this research paper is to gain higher throughput and low end to end delay in highly congested network.